2016
DOI: 10.1371/journal.pone.0157303
|View full text |Cite
|
Sign up to set email alerts
|

All Components of Metabolic Syndrome Are Associated with Microalbuminuria in a Chinese Population

Abstract: Background and AimAlbuminuria is a well-known predictor of poor renal and cardiovascular outcomes and associated with increased risk of all-cause mortality. The study aimed to evaluate the associations between metabolic characteristics and the presence of albuminuria.MethodsThis cross-sectional study included 18,384 adult Chinese who participated in health examinations during 2013–2014. Differences in clinical characteristics were compared for microalbuminuria (MAU) and albuminuria, and between genders. Potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 48 publications
2
7
0
Order By: Relevance
“…BP and fasting glucose were consistently found to be two main risk factors associated with MAU, which was also clearly shown in our study. However, the associations between MAU and abdominal obesity, HDL and TG levels were inconsistent in previous studies 8 9 16. Thus far, two studies have reported an association between MAU and risk of MetS, with ORs of 5.13 (95% CI 1.96 to 13.45) and 2.71 (95% CI 1.69 to 4.36),14 15 which is consistent with our finding.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…BP and fasting glucose were consistently found to be two main risk factors associated with MAU, which was also clearly shown in our study. However, the associations between MAU and abdominal obesity, HDL and TG levels were inconsistent in previous studies 8 9 16. Thus far, two studies have reported an association between MAU and risk of MetS, with ORs of 5.13 (95% CI 1.96 to 13.45) and 2.71 (95% CI 1.69 to 4.36),14 15 which is consistent with our finding.…”
Section: Discussionsupporting
confidence: 87%
“…Some studies have evaluated the relationship between MetS and MAU as a marker for early-stage chronic kidney disease 8–11. Significant associations between MetS and MAU have been demonstrated in Japanese,9 Korean10 12 and Chinese populations 13–16. However, data concerning the relationship between individual MetS components and MAU have been inconsistent, and a causal relationship between MAU and MetS remains unclear despite the predictive value MAU showed in the aforementioned studies.…”
Section: Introductionmentioning
confidence: 99%
“…A recent review showed that microalbuminuria might not simply be regarded as a risk predictor but become itself an independent target for treatment of cardiovascular events [23,24]. Metabolic syndrome and all its components were associated with the presence of microalbuminuria in a health checkup population in China [25]. Our present study showed that level of Log UAE was increasing with the number of suffering diseases increasing, and there was positive correlation between Log UAE and CFPWV.…”
Section: Discussionsupporting
confidence: 55%
“…The cut-offs of BMI were 27 kg/m 2 for mild obesity, 30 kg/m 2 moderate obesity, and 35 kg/m 2 severe obesity (Chu, 2005;Chang et al, 2017). Central obesity was defined by a WC ≥ 90 cm in males and 80 cm in females (Ma et al, 2013), a WHR of over 0.9 in males and 0.85 in females (Lin et al, 2004), and WHtR of over 0.6 (Lee et al, 2016b). All analysis was done using STATA (version 13, StataCorp, TX, United States).…”
Section: Discussionmentioning
confidence: 99%